PENGARUH HARGA DAN IKLAN TERHADAP KEPUTUSAN PENYEWAAN VIRTUAL OFFICE PT. MULTI ENERGI SELARAS (MESO) - Arief Rachmawan Assegaf (Jurnal Ekonomi dan Industri, 2022)
The purpose of this thesis is to find out how much consumer interest in choosing to rent an office with a virtual office system with prices and advertisements can influence consumer decisions of PT. Multi Energi Selaras. The analytical method used is multiple linear regression analysis. The results showed that the price had a negative and insignificant effect on the rental decision, while the advertising had a positive and significant effect on the rental decision. Price partially has a positive and significant effect on rental decisions. Advertising partially positive and significant effect on rental decisions.